The Unintended Consequences of Tax Code Complexity - Stephen Kastoryano (Institute of Labor Economics (IZA), 2025)
This paper reveals how tax complexity, in the form of loopholes and assets overlapping different sections of tax returns, contributes to tax avoidance and evasion. Using administrative data from the Netherlands, it shows how an auditing announcement in 2005 triggered large increases in declared assets and properties, predominantly held by the wealthiest segments of society, in unexpected sections of the tax returns. It further takes advantage of a one-year reduction in the dividend tax rate, which coincided with another auditing announcement in 2007, to more specifically assess strategic spontaneous declarations and shifting among shareholders, particularly those with substantial company holdings. The results highlight taxpayer contingency plans and opportunistic behaviour when declaring previously hidden wealth. They also emphasize how the ambiguity of certain assets' classifications can be coopted to strategically shift wealth in response to new tax policies.
Keywords: H26; H83; K34; 330; tax complexity; tax evasion; tax avoidance; auditing announcements